A Case Study on the Utility of Transcranial Doppler Ultrasound in Acute Stroke Evaluation. Issue 1 (March 2020) - Thibeault, Corey M.; Dorn, Amber Y.; Thorpe, Samuel G.; Canac, Nicolas; Jalaleddini, Kian; Wilk, Seth J.; Shah, Ruchir; Hamilton, Robert B.; Devlin, Thomas G.
The use of transcranial Doppler (TCD) ultrasound in the acute stage of large vessel occlusion diagnosis has, for a number of reasons, not seen widespread adoption. The high temporal fidelity of TCD provides information about the neurovasculature that neurological tests and standard computed tomography (CT) imaging cannot. This presents an opportunity in the early evaluation of patients that can help clinicians make informed decisions. The case study presented here illustrates the complementary information that TCD can provide in a situation where other available tests failed to fully elucidate the underlying pathology.